Language learning and brain reorganization in a 3.5-year-old child with left perinatal stroke revealed using structural and functional connectivity. (April 2016) - François, Clément; Ripollés, Pablo; Bosch, Laura; Garcia-Alix, Alfredo; Muchart, Jordi; Sierpowska, Joanna; Fons, Carme; Solé, Jorgina; Rebollo, Monica; Gaitán, Helena; Rodriguez-Fornells, Antoni
Abstract: Brain imaging methods have contributed to shed light on the possible mechanisms of recovery and cortical reorganization after early brain insult. The idea that a functional left hemisphere is crucial for achieving a normalized pattern of language development after left perinatal stroke is still under debate. We report the case of a 3.5-year-old boy born at term with a perinatal ischemic stroke of the left middle cerebral artery, affecting mainly the supramarginal gyrus, superior parietal and insular cortex extending to the precentral and postcentral gyri. Neurocognitive development was assessed at 25 and 42 months of age. Language outcomes were more extensively evaluated at the latter age with measures on receptive vocabulary, phonological whole-word production and linguistic complexity in spontaneous speech. Word learning abilities were assessed using a fast-mapping task to assess immediate and delayed recall of newly mapped words. Functional and structural imaging data as well as a measure of intrinsic connectivity were also acquired. While cognitive, motor and language levels from the Bayley Scales fell within the average range at 25 months, language scores were below at 42 months. Receptive vocabulary fell within normal limits but whole word production was delayed and the child had limited spontaneous speech. Critically, the child showed clear difficulties in both the immediate and delayed recall of the novel words, significantly differing from an age-matched control group. Neuroimaging data revealed spared classical cortical language areas but an affected left dorsal white-matter pathway together with right lateralized functional activations. In the framework of the model for Social Communication and Language Development, these data confirm the important role of the left arcuate fasciculus in understanding and producing morpho-syntactic elements in sentences beyond two word combinations and, most importantly, in learning novel word-referent associations, a building block of language acquisition.